Oligopoly as a socially embedded dilemma: An experiment - Christoph Engel; Lilia Zhurakhovska (Max Planck Institute for Research on Collective Goods, 2011)
From the perspective of competitors, competition may be modeled as a prisoner's dilemma. Setting the monopoly price is cooperation, undercutting is defection. Jointly, competitors are better off if both are faithful to a cartel. Individually, profit is highest if only the competitor(s) is (are) loyal to the cartel. Yet collusion inflicts harm on the opposite market side and, through the deadweight loss, on society at large. Moreover, almost all legal orders combat cartels. Through the threat with antitrust intervention, gains from cooperation are uncertain. In the field, both qualifications combine. To prevent participants from using their world knowledge about antitrust, we experimentally test them on a neutral matrix game, with either a negative externality on a third participant, uncertainty about gains from cooperation, or both. Uncertainty dampens cooperation, though only slightly. Surprisingly, externalities are immaterial. If we control for beliefs, they even foster cooperation. If we combine both qualifications and do not control for beliefs, we only find an uncertainty effect. If we add beliefs as a control variable, we only find that externalities enhance cooperation, even if gains from collusion are uncertain. Hence the fact that the dilemma of oligopolists is socially embedded matters less than one might have expected.
Keywords: D43; K21; L13; L41; C72; D81; K42; C91; D62; D03; H23; D22; 330; oligopoly; collusion; experiment; uncertainty; negative externalities; prisoner's dilemma; Oligopol; Kartell; Risiko; Externer Effekt; Wettbewerbsbeschränkung; Gefangenendilemma; Test